Altered Interactions Among Resting‐State Networks in Individuals with Obesity. Issue 3 (24th February 2020) - Ding, Yueyan; Ji, Gang; Li, Guanya; Zhang, Wenchao; Hu, Yang; Liu, Lei; Wang, Yuanyuan; Hu, Chunxin; von Deneen, Karen M.; Han, Yu; Cui, Guangbin; Wang, Huaning; et al.
Abstract : Objective: The aim of this study was to investigate alterations in functional connectivity (FC) within and interactions between resting‐state networks involved in salience, executive control, and interoception in participants with obesity (OB). Methods: Using resting‐state functional magnetic resonance imaging with independent component analysis and FC, alterations within and interactions between resting‐state networks in 35 OB and 35 normal‐weight controls (NW) were investigated. Results: Compared with NW, OB showed reduced FC strength in the ventromedial prefrontal cortex and posterior cingulate cortex/precuneus within the default‐mode network, dorsal anterior cingulate cortex within the salience network (SN), bilateral dorsolateral prefrontal cortex‐angular gyrus within the frontoparietal network (FPN), and increased FC strength in the insula (INS) ( P familywise error < 0.0125). The dorsal anterior cingulate cortex FC strength was negatively correlated with craving for food cues, left dorsolateral prefrontal cortex FC strength was negatively correlated with Yale Food Addiction Scale scores, and right INS FC strength was positively correlated with craving for high‐calorie food cues. Compared with NW, OB also showed increased FC between the SN and FPN driven by altered FC of bilateral INS and anterior cingulate cortex‐angular gyrus. Conclusions: Alterations in FC within and interactions between the SN, default‐mode network, and FPN might contribute to the high incentive value of food (craving), lack of control of overeating (compulsive overeating), and increased awareness of hunger (impaired interoception) in OB.